Non-coding RNA expression in cancer stem cell progenies derived from tumours +/-BRAF V600E mutation - Sommerville, Gary (Trinity College (Dublin, Ireland). School of Medicine. Discipline of Histopathology & Morbid Anatomy, 2013)
Cancer has placed a huge burden on the global health system and rising rates in particular cancer types such as lung cancer and melanoma due to smoking and increased UV ray exposure respectively has highlighted the need to combat this disease. Intense research has shed light on the genetic processes that contribute to tumour formation and progression. The BRAF gene is commonly mutated and is thought to be implicated in nearly one third of all human cancers and so represents an important target for novel therapies to combat tumorigenesis. The V600E mutation confers constitutive kinase activity, independent of mitogen initiation, within the MAP-ERK pathway which can lead to aberrant cell signalling. Cancer stem cells have been identified in many human malignancies in a variety of different tissue types ranging from prostate to thyroid.
Keywords: Histopathology, Ph.D.; Ph.D. Trinity College Dublin